THE ‘REALNESS’ KEY TO COMPELLED PASSCODE PRODUCTION. - PELL, GABRIEL (Journal of Criminal Law & Criminology)
This Article explains how the Foregone Conclusion exception to the Fifth Amendment’s privilege against self-incrimination applies to compelled passcode production. The Supreme Court fashioned the Foregone Conclusion exception in connection with the compelled production of documentary evidence. It facilitates government access to real evidence despite the implicit factual communications inherent in a target’s act of producing it (i.e., that the real evidence exists, is accessible, and is what the state demanded). Engaging with the ‘real evidence’ limitation for compelled acts of production, the Article shows that focusing on unlocked devices and/or stored passcodes as the real evidence to be produced in compelled passcode entry cases can resolve splits among courts and commentators while protecting targets from compelled revelation of mere information. This Article goes beyond the technological nuances of encryption to consider realness based on the average user’s experience of a passcode as something that exists outside the mind. Applying Act of Production first principles to the real evidence of unlocked devices and stored passcodes clarifies that the government need not demonstrate pre-production knowledge of the contents of a locked device to satisfy the Foregone Conclusion exception. It further confirms that the reasonable particularity standard often associated with the exception and the Foregone Conclusion exception’s authentication requirement play only limited roles in passcode cases. The Article concludes with a brief explanation of how the first-principles approach to compelled passcode production can also demystify compelled use of biometrics to unlock digital devices.